ASCE seven wonders of the modern world - Kwok, Kenneth Yong Koon. (2009)
In this report, the current Seven Wonders of the Modern World by American Society of Civil Engineers (ASCE) will be reviewed and updated. Thereafter, they will be classified into their respective categories. Over the course of the project, many different disciplines in the civil engineering industry will be explored. For example geotechnical, structures, coastal, steel, reinforce concrete, management, transport and environment. In the process, the student will be able to better understand the progress in technology of the civil engineering construction over the years. With a little more knowledge on how the construction industry operates, the student will be able to relate the experiences of seasoned engineers to our younger generation, stressing on the importance and contribution civil engineers have on our society. As a result, attract more talents into the civil engineering industry for the better of our environment and all mankind.